2015
DOI: 10.1177/1354068815604823
|View full text |Cite
|
Sign up to set email alerts
|

The far-right, immigrants, and the prospects of democracy satisfaction in Europe

Abstract: This paper examines the consequences of the far-right in shaping foreign-born immigrants' satisfaction with the way democracy works in their host country. It posits that while electorally successful far-right parties undermine democracy satisfaction, the magnitude of this effect is not uniform across all first-generation immigrants. Instead, it depends on newcomers' citizenship status in their adopted homeland. The analyses using individual-level data collected as part of the five-round European Social Survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 93 publications
0
6
0
4
Order By: Relevance
“…On a similar note, Minkenberg (2001) argues there has been a transformation in the concept of the 'people' where anti-immigrant parties exercise executive power, shifting from the encompassing demos to the more exclusive ethnos, excluding immigrants from the democratic society. The potential negative influence of anti-immigrant party presence is supported by findings indicating a negative impact of anti-immigrant party strength on satisfaction with democracy among immigrant non-citizens cross-nationally in Europe (Just 2017). The influence of anti-immigrant party parliamentary representation on political participation, however, remains unexplored.…”
Section: Anti-immigrant Party Presencementioning
confidence: 97%
See 1 more Smart Citation
“…On a similar note, Minkenberg (2001) argues there has been a transformation in the concept of the 'people' where anti-immigrant parties exercise executive power, shifting from the encompassing demos to the more exclusive ethnos, excluding immigrants from the democratic society. The potential negative influence of anti-immigrant party presence is supported by findings indicating a negative impact of anti-immigrant party strength on satisfaction with democracy among immigrant non-citizens cross-nationally in Europe (Just 2017). The influence of anti-immigrant party parliamentary representation on political participation, however, remains unexplored.…”
Section: Anti-immigrant Party Presencementioning
confidence: 97%
“…While the literature attempting to explain this development is extensive (Rydgren 2003;Norris 2005;Arzheimer 2009), the potential impact on those who are actually targeted by the conflictresidents with the immigrant backgroundhas received less attention. Positioned in the centre of the debate, their presence is often used as an explanation for increased anti-immigrant attitudes, but their own reactions to the hostile socio-political context has only recently begun to attract scholarly focus (Maxwell 2009;Connor 2010;Heath and Demireva 2014;Just and Anderson 2014;Pérez 2015;Just 2017). My paper contributes to this nascent literature that shifts the focus from natives to immigrants, studying the influence of contextual hostility within the targeted group.…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies testing the impact of contextual hostility have found negative effects on immigrant's relation to the political society. Anti-immigrant party parliamentary representation and restrictive immigration policies have for instance been shown to lower satisfaction with democracy among non-citizens (Just 2017) and decrease applications for citizenship (Jones-Correa 2001;Van Hook, Brown, and Bean 2006). Contextual hostility has also been found to mobilize political participation (Jones-Correa 2001; Ramakrishnan and Espenshade 2001; Pantoja, Ramirez, and Segura 2001; Okamoto and Ebert 2010; but see Just and Anderson 2014 for demobilizing findings), which at first may appear as an exception to the negative impact.…”
Section: Theory and Previous Researchmentioning
confidence: 99%
“…Anti-immigrant sentiments are one of many societal consequences following international migration. Scholars have traditionally attempted to explain the development of hostile attitudes towards immigrants, but a growing literature is shifting the attention, focusing instead on the impact of hostility on immigrant residents (Maxwell 2009;Connor 2010;Heath and Demireva 2014;Just and Anderson 2014;Just 2017;Pérez 2015). My paper engages with this literature, studying the hostility immigrants face in their surrounding environment and how such contextual hostility influences immigrant youths' attitudes towards the host society.…”
Section: Introductionmentioning
confidence: 99%
“…It suggests that people acquire political orientations during formative years, and that, once acquired, these orientations tend to persist over time, as individuals avoid or reject messages that contradict views they already hold (Festinger, 1957;Sears & Levy, 2003;Zaller, 1992). Consistent with this perspective, scholars found that socialization in undemocratic or repressive regimes indeed structures immigrants' attitudes toward democratic governance (Bilodeau, 2014;Bilodeau, McAllister, & Kanji, 2010;Just, 2017;McAllister & Makkai, 1992) and influences the patterns of their political engagement in adopted homeland (Bilodeau, 2008;Just & Anderson, 2012;White, 2017).…”
mentioning
confidence: 99%